2016
DOI: 10.1136/gutjnl-2016-312456
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants in the sucrase–isomaltase gene associate with increased risk of irritable bowel syndrome

Abstract: Objective IBS is a common gut disorder of uncertain pathogenesis. Among other factors, genetics and certain foods are proposed to contribute. Congenital sucrase–isomaltase deficiency (CSID) is a rare genetic form of disaccharide malabsorption characterised by diarrhoea, abdominal pain and bloating, which are features common to IBS. We tested sucrase–isomaltase (SI) gene variants for their potential relevance in IBS. Design We sequenced SI exons in seven familial cases, and screened four CSID mutations (p.Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
129
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 39 publications
4
129
1
3
Order By: Relevance
“…Trials assessing effect by genotype: Genetic variants more common in IBS patients compared to healthy controls …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
“…Trials assessing effect by genotype: Genetic variants more common in IBS patients compared to healthy controls …”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
“…Congenital deficiencies of sucrase‐isomaltase and trehalase are well described, being relatively common in Greenland and Alaska but not in the USA or Europe, and result in gastrointestinal symptoms consistent with those induced by carbohydrate malabsorption . Recent studies in adult populations have indicated that the presence of common and rare polymorphisms of sucrase‐isomaltase that are associated with reduced activity of the expressed protein are more common in patients with non‐constipation‐predominant patients with IBS with odds ratio of 1.36 for the more common 15Phe variant . The practice of measuring hydrolase activities in duodenal biopsies is relatively common in pediatrics, and reduced activities on one or combined enzymatic activities are frequently observed; for example, in a systematic review of more than 30,000 tests from a spectrum, of patients, lactase was reduced in 39%, maltase in 13%, sucrase in 9%, and isomaltase in 9%, and pan‐disaccharidase deficiencies may occur in up to 10% .…”
Section: Introductionmentioning
confidence: 99%
“…We exclude those with well‐recognized conditions such as deficiencies of disaccharidases or other carbohydrate‐digesting enzymes (e.g., lactase, trehalase and sucrase‐isomaltase) which may have a similar presentation. The role of acquired mucosal disaccharidase deficiencies is still relatively uninvestigated and further studies are warranted …”
Section: Introductionmentioning
confidence: 99%
“…The role of acquired mucosal disaccharidase deficiencies is still relatively uninvestigated and further studies are warranted. 6,7 Most of the patients we describe would be classified as having functional bowel syndrome using the Rome IV criteria. 8 With an estimated global prevalence of 11.2%, functional bowel syndromes are common, which results in many patients seeking medical help because of these symptoms.…”
Section: Introductionmentioning
confidence: 99%